A cloud based 3-tier data security framework for industrial internet of things - Mirador G. Labrador; Abegail Bordios; Weiyan Hou (Institute of Advanced Engineering and Science, 2021)
The convergence of microelectronics and micromechanical system within a sensing device, the proliferation of wireless communication, and the use of software-driven equipment are already changing the landscape of the manufacturing industries. This situation compels the industries to adopt industrial internet of things (IIoT) systems and processes with the main objective-to improve the processes and increase production. However, it is undeniable that despite IIoT advantages, it posed significant issues on the security and privacy on industry automation especially along data generation and control system. Hence, this paper proposes a cloud based 3-tier data security framework that performs two-level security verification processes. The framework has been tested and validated using an experimental industry automation system and has been found to be functionally effective with an acceptable handoff delay.